Consumer Behavior in Making Purchasing Decisions on the Shopee Program On-Time Guarantee : - Rundika Pratiwi, Endah; Tri Ananda, Sabilla (Asosiasi Ahli Administrasi Indonesia, 2024)
The phenomenon of Indonesians doing online shopping activities in the marketplace has continued to increase in recent years, but it has not been directly proportional to consumer satisfaction. Consumers are disappointed that orders do not arrive on time. The study aims to determine consumer behavior when making purchasing decisions on Shopee's On-Time Guarantee. The research was conducted using a qualitative approach, namely interviews and Focus Group Discussions. The research findings explain that the On-Time Guarantee is closely related to the formation of consumer behavior in making purchasing decisions, such as recognizing problems, searching for information, evaluating alternatives, purchasing decisions and evaluating post-purchase behavior. Informants gather information from social media, Google, and brand ambassadors on television. In evaluating alternatives, informants compare Shopee's service quality with competitors and the efficiency of order delivery time. Positive feedback from friends, promotions, delivery speed, and ease of handling influence purchase decision-making. Innovative technologies such as real-time delivery and automatic notifications on the app affect consumer satisfaction. The conclusion is that informants will make repeat purchase decisions in the future and recommend Shopee to their social environment, which can increase Shopee's customer base. Informants' satisfaction with Shopee's 'On-Time Guarantee' has a positive impact on consumer loyalty.